Die Wiedergabe deutscher Abtönungspartikeln im Polnischen unter Satzarten- und Intentionsaspekt - Duch, Justyna (Wydawnictwo Naukowe UAM, 2008)
Modal particles can be strategically used by the speaker to specify the illocutionary content, which can have different consequences on the pragmatic and communicative level. This paper is an attempt to present German and Polish modal particles according to the intention of the speaker and sentence types. This paper gives also an insight into problem of the translation of modal particles.
Keywords: Abtönungspartikeln; Intentionsaspekt